The Assertive Technique of Online Group Counseling on Student Academic Resilience - Evia Darmawani Evia Darmawani; Endang Surtiyoni; Nurlela Nurlela; Ramtia Darma Putri (Bisma The Journal of Counseling, 2023)
Academic resilience, namely the ability of students to achieve academic success, even in situations that pressure and prevent them from achieving success. The reality on the ground shows that after implementing online learning, the level of student resilience tends to be low, so to overcome these problems, students need special guidance from counselors. This study aims to provide an overview of changes in student behavior in attending Onelin lectures after group counseling using assertive techniques. This research belongs to the type of quantitative research using class action methods. The subjects involved in this study were six students who experienced decreased resilience during the lecture process. Data collection in the study was carried out using observation, interview, documentation, and questionnaire methods. The data obtained in the study were then analyzed using percentage analysis techniques. The results of the research analysis showed that there was an increase in students' pre-test and post-test scores during the research cycle. The results show that 33% of students have high resilience in completing eight semesters of lectures, 50% have moderate resilience and can complete education in 9 semesters, and 17% have low resilience. These results then show that, in general, the application of group counseling assertive training techniques can significantly restore resilience in students, which is shown by the attitude of surviving and struggling to survive in various situations that interfere with the achievement of learning outcomes.